Validity of heart rate-based models for estimating oxygen uptake during tennis play - Baiget, E.; Iglesias, X.; Rodríguez, F. A. (The Journal of Strength and Conditioning Research, 2020)
This study aimed to assess the validity of an on-court tennis test (specific endurance tennis test [SET-Test]) and 2 heart rate (HR)-based methods for estimating oxygen uptake (VO2) in competitive tennis players. Thirty-five male players performed a SET-Test to relate test duration (minutes) and VO2. Two weeks later, 16 players performed a simulated match play set where HR and VO2 (VO2-PLAY, criterion value) were measured and then compared with VO2 values predicted from the HR/VO2 linear regression equations derived from the SET-Test (pVO2-TEST) and from the one set match play (pVO2-PLAY). Test duration and VO2-TEST were strongly correlated (r2 = 0.821, p < 0.001, SEE = 5.6 ml/kg/min), indicating that SET-Test outcome is a somewhat good indicator of aerobic fitness in tennis players, likely to be useful for training purposes. pVO2-PLAY and VO2-PLAY (criterion value) were strongly correlated (r2 = 0.832, p < 0.001) and SEE was moderate (3.5 ml/kg/min = 11.5%). pVO2-TEST differed from the criterion (32.4 ± 10.7 vs. 30.8 ± 8.6 ml/kg/min, p < 0.001) and, although strongly correlated (r2 = 0.689, p < 0.001), an overestimation occurred (mean Delta = 1.6 ml/kg/min = 4.9%), yielding a high SEE (4.8 ml/kg/min = 15.6%). We conclude that (a) SET-Test performance is a valid and moderately accurate predictor of VO2; and (b) the individual HR-VO2 regression equation generated during tennis match play predicts VO2 with greater accuracy than the regression derived from the SET-Test.